"If it looks like a duck…" – why humans need to focus on different approaches than insects if we are to become efficiently and effectively ultrasocial. (2016) - Aitken, Kenneth John
Abstract: The parallels between the agricultural successes of ultrasocial insects and those of humans are interesting and potentially important. There are a number of important caveats, however, including the relative complexities of insect reproduction, their more rigidly determined altricial patterns of social behaviour, the roles of post-reproductive group members, and differences in the known factors involved in ultrasocietal collapse.